СОЦИАЛЬНО-ФИЛОСОФСКОЕ ОСМЫСЛЕНИЕ ФЕНОМЕНА РЕКЛАМЫ - Васильева, Л. А. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
Автор досліджує онтологічний та аксіологічний зріз феномена реклами як визначальних у соціально- філософському аспекті даного соціокультурного простору. Автор доводить, що як одне з інноваційних явищ сучасної комунікативної дійсності, реклама транслює свою історію через так звані «інформаційні революції», які мали місце в окремі визначені економічно-культурні періоди суспільства. Саме становлення феномену реклами як діяльності, творчості і продукту таїть у собі різноманітні тлумачення її генезису, змісту і функцій. Васильева Л. СОЦИАЛЬНО-ФИЛОСОФСКОЕ ОСМЫСЛЕНИЕ ФЕНОМЕНА РЕКЛАМЫ. Автор исследует онтологический и аксиологический срез феномена рекламы как определяющих в социально- философском аспекте данного социокультурного пространства. Автор доказывает, что как одно из инновационных явлений современной коммуникативной действительности, реклама транслирует свою историю через так называемые «информационные революции», которые имели место в определенные экономико-культурные периоды общества. Именно становление феномена рекламы как деятельности, творчества и продукта таит в себе различные толкования ее генезиса, содержания и функций. Ключевые слова: феномен рекламы, коммуникативная действительность, «информационные революции». L. Vasiljeva. THE SOCIAL-PHILOSOPHICAL PERCEPTION OF PHENOMENON OF ADVERTISEMENT. The author explores the ontological and axiological cutoff of the phenomenon of advertisement, as a definer in the socio-philosophical aspects of the social and cultural phenomenon. The author argues that as one of the innovative phenomenon of modern communicative reality, advertisement broadcasts its history through the so-called "information revolutions" that occurred in certain specified periods of economic-cultural society. In the article the author stresses that the development of a business like advertisement, creativity and product carries a different interpretation of its genesis, contents and functions. Key words: phenomenon of advertisement, communicative reality, "information revolutions".